If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = -2(k + 5) + -15 Reorder the terms: -9 = -2(5 + k) + -15 -9 = (5 * -2 + k * -2) + -15 -9 = (-10 + -2k) + -15 Reorder the terms: -9 = -10 + -15 + -2k Combine like terms: -10 + -15 = -25 -9 = -25 + -2k Solving -9 = -25 + -2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2k' to each side of the equation. -9 + 2k = -25 + -2k + 2k Combine like terms: -2k + 2k = 0 -9 + 2k = -25 + 0 -9 + 2k = -25 Add '9' to each side of the equation. -9 + 9 + 2k = -25 + 9 Combine like terms: -9 + 9 = 0 0 + 2k = -25 + 9 2k = -25 + 9 Combine like terms: -25 + 9 = -16 2k = -16 Divide each side by '2'. k = -8 Simplifying k = -8
| 2(s+1)=-2 | | -3r+-1=2r+16+-7 | | W/8=-26 | | -(c+14)=2 | | 4x^2-21x-135=0 | | 99=-6m-(7m+5) | | 3x-14+2(x-4)=2x-2 | | 19=2(b+20)-(-17) | | 1.7=0.22 | | (7*35)+(x*.14)=(7*70)+(x*.07) | | 107-11b=-1b+37 | | y-4/-3=9 | | -32(11x)+27(14x)=0+-296 | | 0=16+4x+x^2 | | =(9x)+(3x-5) | | 12=7-3x | | 3d+2d= | | 2(1+6x)+2(3-6x)=7x-3x | | (9x)+(3x-5)= | | 50+60x=-84+210x | | 35+(x*.14)=70+(x*.07) | | 35+2b=5b+11 | | 50000d=238900 | | G(x)=3-x | | x=2+0.2t | | 99-14b=-5b+63 | | 0.2*0.02= | | (3x-1)+2(2x+6)=5x-3 | | 3b+4b-2=26 | | 0.25x+0.5x=1.5 | | 3(2v+1)-5= | | sqrt(2x)-(1)/(sqrt(2))=sqrt(8x) |